Synthesis of ErBa2Cu3O7−δ Superconductor Solder for the Fabrication of Superconducting Joint between Gdba2cu3o7−δ Coated Conductor - Zili Zhang; Lei Wang; Jianhua Liu; Qiuliang Wang (Crystals, 2019)
ErBa2Cu3O7−δ (Er123) superconductor is one of the best candidates of superconductor solder for the fabrication of superconducting joint between GdBa2Cu3O7−δ (Gd123) coated conductor, due to its high Tc value (93 K) and highest optimized oxygen annealing temperature among RE123 compounds. In this paper, we systematically research the effect of sintering parameters on the phase formation, microstructure and superconducting properties of Er123 powder. The optimized synthesis route to acquire high purity Er123 powder with as good superconducting properties as Gd123 has been uncovered. The melt temperature of Er123 with different dopant compared to Gd123 is also investigated, and the feasible operating temperature range of Er123 superconductor solder is discussed. This work reveals a very important starting point on fabrication high-quality superconducting joint between the commercial Gd123 coated conductor, which can further improve the development of the persistent operating mode on ultra-high field nuclear magnetic resonance and magnetic resonance imaging.